Interactions between menstrual cycle, training load and strength performance in elite female weightlifters - Schatz, P.; Ullrich, F.; Siegert, F.; Legerlotz, K.; Diel, P.; Isenmann, E. (Journal of Science and Medicine in Sport, 2026)
Objectives This study aimed to investigate the impact of the menstrual cycle on strength performance, training load, and subjective recovery in elite female weightlifters. Design A six-month observational study involving eight eumenorrheic female weightlifters (age: 24.5±5.3 years; body weight: 72±11 kg), with menstrual cycle phases identified through diaries and daily temperature measurements. Saliva samples were collected every two days for three months to confirm eumenorrheic cycles. Methods Back squat strength was assessed during training sessions using an inertial measurement unit (ENODE Sensor). Subjective recovery was evaluated via the Short Recovery and Stress Scale. Results Out of 32 potential cycles, 24 (75%) were recorded, with a mean cycle length of 27.0±2.5 days. No direct impact of menstrual cycle phases on back squat performance was found. However, during moderate training weeks, a significant performance decrease was observed in the late luteal phase compared to the early follicular phase and during low training weeks. Short Recovery and Stress Scale scores showed no significant changes across phases. Conclusions The menstrual cycle alone does not significantly affect strength capacity or perceived recovery in elite weightlifters. However, strength performance is significantly reduced in the late luteal phase when training load is moderate. Further studies should examine the menstrual cycle's interaction with other influencing factors.